Coeducational Methodology Used by Physical Education Teachers and Students Perception of It - Cofre-Bolados, C (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Background: In physical education (PE), the methodology used to develop coeducation must consider the tastes and preferences of students. The purpose of this work was to analyze how teachers work with different aspects of PE classes and how their work is perceived by students. Methods: The sample was formed of 176 teachers and 1136 secondary school students. The research design was descriptive. The instruments used were the Questionnaire of Coeducational Aspects in Physical Education for teachers and the Questionnaire of Perception of Equality and Discrimination in Physical Education for Students. Results: The different statistical analyses showed significant differences in how male and female teachers assigned responsibility to the students. With regard to the students, significant differences were found between boys and girls in their opinions of how their teachers apply the same rules to all the students. Conclusions: Differences exist between male and female teachers in regard to control of the area used for motor activity. With regard to the students, girls perceive to a greater extent than their male counterparts that the activities in PE classes promote equality in the improvement of their capacities. © 2018 by the authors.